The pattern of pediatric malignancy and outcome in Khartoum Oncology hospital, Sudan: A 15-year single-center experience - Mohammed Awad Abdalla; Zeinab Mohammed (Elsevier, 2024)
Background: Sudan is a country with limited resources. The pattern of malignancies is unknown due to the lack of a national registry. Khartoum's oncology hospital is the largest in the country. Large hospital data might reflect the country's profile. This study investigates the 15-year disease distribution and survival rates of children with malignant diseases at Khartoum Oncology Hospital (KOH). Material and methods: Children 0-15 years with histologically confirmed malignancy were followed from 2005 to 2019 in KOH, Sudan. The disease pattern and overall survival (OS) and event-free survival (EFS) were estimated by the Kaplan-Meier method. Results: We studied 4343 electronically registered and hard copies of patients. Children constitute 4% of all center patients. The male-to-female ratio was 1.5.Seventy-two percent of patients are between 1 and 10 years old. The abandonment rate is high (32.2%) and contributes to low survival. Acute lymphoblastic leukemia, non-Hodgkin lymphoma, Hodgkin lymphoma, Wilms tumor, and retinoblastoma were the most common malignancies. The EFS was 47.4%, and OS was 49.3%. Conclusion: Malignancy was more common in males. The malignancy pattern was similar to that in other African countries. Abandonment rates are high. A cancer registry is needed to determine the malignancy pattern in the pediatric population.